Present and future mass standards for the LNE watt balance and the future dissemination of the mass unit in France. (18th July 2016) - Pinot, Patrick; Beaudoux, Florian; Bentouati, Djilali; Espel, Patrick; Madec, Tanguy; Thomas, Matthieu; Silvestri, Zaccari; Ziane, Djamel; Piquemal, François
Abstract: The value of the Planck constant h was determined in 2014 by means of the LNE watt balance experiment. The relative standard uncertainty was 31 parts in 10 8 . This first determination was performed in air with a 500 g mass standard made from XSH Alacrite. The main uncertainty components in air associated with the mass involve the calibration, the mass stability, the buoyancy correction and the magnetic interaction correction. The combined relative uncertainty due to the mass is 7.2 parts in 10 8 . The use in 2016 of a mass standard made from platinum iridium alloy significantly reduces the component of uncertainty arising from the mass standard for a Planck constant measurement either in air or under vacuum. The relative uncertainty due to this contribution is estimated to be about 3 parts in 10 8 in air and one part in 10 8 under vacuum. The future system for the dissemination of the mass unit using the LNE watt balance will be based on a primary realization with three 500 g mass standards made from platinum–iridium alloy, pure iridium and Udimet 720 respectively, coupled with a pool of kilograms made from different materials. Pure iridium and Udimet 720 are new materials to make reference mass standards proposed by CNAM and LNE respectively and have never been used by any NMI for manufacturing mass standards until now. Some new results concerning their surface behavior are given.